Analisis Kausalitas Antara Korupsi, Investasi, Pengangguran dan Pertumbuhan Ekonomi - Haldi, Muhammad (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2023)
This study analyzes the causality and short-term and long-term relationships between corruption, investment, unemployment, and per capita economic growth in twenty-two Asia-Pacific countries from 2012 to 2020. This study uses the Granger causality approach and the Vector Error Correction Model to answer the problem in this study. The empirical results show that corruption and per capita economic growth has a two-way causality, and the unemployment rate and per capita economic growth only have a one-way causality. On the other hand, the rest have no causal relationship. In the short term, corruption does not significantly affect per capita economic growth and unemployment. However, significant and negative in influencing the level of investment. Meanwhile, in the long term, corruption significantly and negatively affects economic growth per capita. The level of investment and unemployment has a significant and positive effect on economic growth per capita. Therefore, corruption is an obstacle to economic growth and not a